Disclosure of Islamic Social Reporting in Sharia Banks: Case of Indonesia and Malaysia - Wardani, Marita Kusuma; Sari, Dea Devita (Institut Agama Islam Negeri Surakarta, 2018)
This study aims to analyze the effect of profitability, leverage, the board of Commissioners and the number of sharia supervisory board of the Islamic Social Reporting (ISR) Islamic banks in Indonesia and Malaysia during the period 2014-2016. The dependent variable in this study is Islamic Social Reporting. While the independent variable is profitability, leverage, the board of Commissioners and the number of sharia supervisory board. The population in this study includes all Islamic banks. Samples were selected using a purposive sampling method and acquired 12 units of Islamic banks in Indonesia and 15 units of Islamic banks in Malaysia. Analysis of the data to test the hypothesis used multiple regression (OLS). The results showed that the profitability of significant positive effect on the disclosure of ISR in Islamic banks in Indonesia, but not with Islamic banks in Malaysia. The study also produced findings that the Board of Commissioners of significant positive effect on the disclosure of ISR in both countries. Furthermore, leverage and the number of sharia supervisory boards do not significantly affect the ISR.